Effect of injection pressure and fluid volume and density on the jet dispersion pattern of needle-free injection devices. (October 2015) - Grant, Tyler M.; Stockwell, Kevin D.; Morrison, Jason B.; Mann, Danny D.
Abstract : Needle-free injection devices improve vaccinator safety and optimise vaccine delivery time by eliminating the use of needles involved with traditional vaccination techniques. Of significant importance is a full understanding of the relationships that exist between the injection properties and the depth and shape of the injectate's dispersion. Work has been done to characterise the distribution of human needle-free injection devices, but little research has been conducted on livestock injections, which operate at much higher pressures and volumes. Therefore, the aim of this research was to characterise the injection profile of a livestock needle-free injection device while varying the injection pressure and fluid volume and density. Water and porcine circovirus vaccine were injected into ballistic gelatin blocks and the injection mechanism was captured using high-speed photography. The volume was varied between 1.0 and 2.5 ml and orifice pressure between 40 and 220 MPa. It was found that pressure influenced the depth of penetration, but had little effect on the shape of the injection profile. In contrast, the volume and density increased the penetration depth and varied the dispersion pattern. These results can be used to better understand how the injection profile of a needle-free injection device changes given an initial set of parameters. This will be important for developing administration protocols that successfully deliver intradermal, subcutaneous, and intramuscular livestock injections. Highlights: Needle-free livestock injection is at higher pressure and volume than for humans. Injections into ballistic gelatin captured using high-speed photography. Pressure influenced penetration depth but had little effect on injection profile. Volume and density increased penetration depth and varied the dispersion pattern. Results can be used to predict the injection profile of a needle-free injection.